Analisa Pengaruh Arus & Variasi Jarak Kampuh Las Berdasarkan Kekuatan Uji Tarik & Radiografi Pada Proses Pengelasan Material Baja ASTM A36 - Setiawan, M. Yusuf; Saleh, Moch. (Madani: Jurnal Ilmiah Multidisiplin, 2024)
SMAW welding was used to weld E6010 electrodes with a diameter of only 3.2 mm to ASTM A36 steel in this study. Welded with three currents, namely 90A, 100A, 110A and a welding gap of ±2 mm and ±3 mm. To determine the strength of the welded joint, a tensile test is carried out on the material being welded, and welding defects are monitored using radiography. It can be seen that defects in welded joints with an initial width of 2 mm are relatively low if the welded joint has a weld gap of approximately 3 mm. The highest yield strength was shown by material welded with a current of 90A, namely 367.83 MPa, followed by material welded at 110 A, namely 366.21 MPa. The highest tensile strength was shown by material welded at 110 A, namely 474.78 MPa, followed by material welded at 90A, namely 469.67 MPa. The highest results were found in material welded at a weld seam distance of 3 mm. Elongation in these conditions was 22.9% and 24% respectively.